Coupling coefficients of different disk microresonators with whispering gallery modes (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2017)
The coupling coefficients of the disk microresonators consisting of different dielectrics are presented. The analytical expressions for the coupling coefficients are obtained. The basic regularities of the coupling coefficient changing on the structure parameter variations are considered. The coupling coefficients as functions of main structure parameters are studied. The calculation results of the transmission coefficients as well as the reflection coefficients of the bandpass filters building up on different disk microresonators with different modes are presented. The S-matrix frequency dependences of the bandpass filters on different disk microresonators in the infrared wavelength range are calculated. The necessary for acceptable measure of the scattering dielectric Q-factor values are determined. The amplitude-frequency characteristics of the bandpass filters on the vertically coupled as well as laterally coupled disc microresonators are investigated. Most optimal configurations of coupled microresonators allowing to achieve the best scattering characteristics are determined. It's shown that using of microresonators with whispering gallery modes relatively easy allows to obtain frequency-symmetrical characteristics of the filters.